ADABTING TEXT TYPES AND REGISTERS - Oydinoy Hamidova; Ahmedov A (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Adapting text types and registers involves adjusting the style, tone, and language of a piece of writing or speech to suit the specific context and audience. For example, when writing a formal report for a business audience, the language used would be more technical and professional compared to writing a personal email to a friend. Similarly, when speaking to a group of children, the language used would be simpler and more engaging compared to speaking to a group of academics.